(3QSGdI aj CNP GdCHYGOs - (3CHh eMeO Gdehdj GdRjJjs ((3OeTb s)
(3ChdgG (B:s
(3GYdeJfi GYRc Gddg HWGYJg Gfce GMJLJe Edi eYQaI GQJaGY MUf ef MUhf s
(3BNQgG (B:s
(3hai gPG GdHGH gdc GdfGS ai Ojfge hOfjGge Je cJGH CHj eMeO Gdehdi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGef hGdYTQhfs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs